Oligodendrocyte responses to buprenorphine uncover novel and opposing roles of μ-opioid- and nociceptin/orphanin FQ receptors in cell development: Implications for drug addiction treatment during pregnancy - Eschenroeder, Andrew C. (2011)
Although the classical function of myelin is the facilitation of saltatory conduction, this membrane and the oligodendrocytes, the cells that make myelin in the central nervous system (CNS), are now recognized as important regulators of plasticity and remodeling in the developing brain. As such, oligodendrocyte maturation and myelination are among the most vulnerable processes along CNS development. We have shown previously that rat brain myelination is significantly altered by buprenorphine, an opioid analogue currently used in clinical trials for managing pregnant opioid addicts. Perinatal exposure to low levels of this drug induced accelerated and increased expression of myelin basic proteins (MBPs), cellular and myelin components that are markers of mature oligodendrocytes. In contrast, supra-therapeutic drug doses delayed MBP brain expression and resulted in a decreased number of myelinated axons. We have now found that this biphasic-dose response to buprenorphine can be attributed to the participation of both the mu-opioid receptor (MOR) and the nociceptin/orphanin FQ receptor (NOP receptor) in the oligodendrocytes. This is particularly intriguing because the NOP receptor/ nociceptin system has been primarily linked to behavior and pain regulation, but a role in CNS development or myelination has not been described before. Our findings suggest that balance between signaling mediated by (a) MOR activation and (b) a novel, yet unidentified pathway that includes the NOP receptor, plays a crucial role in the timing of oligodendrocyte maturation and myelin synthesis. Moreover, exposure to opioids could disrupt the normal interplay between these two systems altering the developmental pattern of brain myelination.